Biological correlates of psychopathy: a brief review. Issue 2 (3rd June 2014) - Debowska, Agata; Boduszek, Daniel; Hyland, Philip; Goodson, Simon
Abstract : Purpose: – The purpose of this paper is to present and provide a critical review of most recent studies inquiring into brain abnormalities in psychopathy. Design/methodology/approach: – The authors provide an overview of the findings of neurobiological studies conducted in the last five years. Publications chosen for review were found using Web of Science, PsycINFO and Scopus search engines. Findings: – Data in the literature reveal that psychopathy is associated with brain abnormalities in frontal and temporo-limbic regions, i.e. regions responsible for moral decision making, emotional processing and learning. Additionally, interactions between the brain areas have been identified as crucial for the development of psychopathic personality traits. Research findings suggest that the flow of impulses between the frontal cortex and temporo-limbic structures in psychopaths is significantly hindered. Originality/value: – The current paper provides an in-depth review of most recent neurobiological studies inquiring into brain abnormalities associated with psychopathic personality traits. Moreover, a particular attention has been paid to identifying abnormalities in brain structures not previously studied in relation to psychopathy (e.g. mirror neuron system, white matter connections).